2010
DOI: 10.1002/hbm.20925
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the hemodynamic modes associated with interictal epileptic activity using a deformable model‐based analysis of combined EEG and functional MRI recordings

Abstract: Simultaneous electroencephalography and functional magnetic resonance imaging (EEG/fMRI) have been proposed to contribute to the definition of the epileptic seizure onset zone. Following interictal epileptiform discharges, one usually assumes a canonical hemodynamic response function (HRF), which has been derived from fMRI studies in healthy subjects. However, recent findings suggest that the hemodynamic properties of the epileptic brain are likely to differ significantly from physiological responses. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 64 publications
(76 reference statements)
3
27
0
1
Order By: Relevance
“…For example, positive as well as negative signal changes were found , or extensive ones and such remote to regions which were identified as potential seizure origins by other established diagnostic tools (Gotman, 2008). This motivated another wave of principally methodological studies probing different hemodynamic response functions to epileptic discharges Grouiller et al, 2010;Hawco et al, 2007;Jacobs et al, 2008;Jacobs et al, 2007;Kang et al, 2003;Lemieux et al, 2008;Lu et al, 2006; Evolution of EEG-fMRI acquisition and concepts applied to epilepsy. EEG-fMRI in epilepsy was initially applied to map the area of cortical tissue that generates interictal epileptic discharges (a-d), later this was extended by group studies revealing processes common to epilepsy syndromes (e, f), and recently, an area commonly involved across a variety of focal epilepsies was proposed (g).…”
Section: Eeg-fmri Applications In Epilepsymentioning
confidence: 98%
“…For example, positive as well as negative signal changes were found , or extensive ones and such remote to regions which were identified as potential seizure origins by other established diagnostic tools (Gotman, 2008). This motivated another wave of principally methodological studies probing different hemodynamic response functions to epileptic discharges Grouiller et al, 2010;Hawco et al, 2007;Jacobs et al, 2008;Jacobs et al, 2007;Kang et al, 2003;Lemieux et al, 2008;Lu et al, 2006; Evolution of EEG-fMRI acquisition and concepts applied to epilepsy. EEG-fMRI in epilepsy was initially applied to map the area of cortical tissue that generates interictal epileptic discharges (a-d), later this was extended by group studies revealing processes common to epilepsy syndromes (e, f), and recently, an area commonly involved across a variety of focal epilepsies was proposed (g).…”
Section: Eeg-fmri Applications In Epilepsymentioning
confidence: 98%
“…Likewise, in case of epilepsy, some authors reported a linear relationship between discharges and hemodynamic responses (Mirsattari et al 2006), while others showed departures from linearity ). In addition, several puzzling observations of negative BOLD deflections with respect to generalized or focal spikes have been made Salek-Haddadi et al 2006;Gotman et al 2006;Grouiller et al 2010). The spike shape, in particular its late slow wave part, has been proposed to have an impact on the sign of the hemodynamic response .…”
Section: Introductionmentioning
confidence: 95%
“…IED-related multifocal positive and negative haemodynamic changes have been commonly revealed both distant and local to the presumed epileptic focus Salek-Haddadi, Diehl et al 2006). These findings have raised questions about the behaviour of the networks associated with epileptiform discharges, and in particular how haemodynamic responses are coupled to these events (Logothetis 2008) as the neurovascular coupling could be altered in pathological states such as epilepsy (Hamandi, Laufs et al 2008;Lemieux, Laufs et al 2008;Grouiller, Vercueil et al 2010;Masterton, Harvey et al 2010). Moreover, scalp EEG-fMRI fails to reveal convincing haemodynamic changes in a significant proportion of cases, possibly due to the limited sensitivity of scalp EEG and consequent poor characterisation of the baseline and inefficient modelling of the fMRI signal (Al-Asmi, Benar et al 2003;Salek-Haddadi, Diehl et al 2006).…”
Section: Introductionmentioning
confidence: 99%